Mit totalitaryzmu i Platońska filozofia demokracji - Paradowski, Ryszard (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
A certain trend in political philosophy has associated Plato with a totalitarian tradition, which is disputed in this paper. The author argues that Plato could be included in the political philosophy of a democratic type, referring to the interpretation of the theory of ideas, presented in the text. This interpretation involves a certain understanding of the idea of the Good and the two principal methods of defining it, as well as ‘Plato’s dilemma’ (the Good above the Demiurge versus the Demiurge above the Good), and a peculiar Platonic way to resolve this dilemma. Additionally, the author confronts Plato’s dilemma with the axiological duality of the cultural message conveyed by the Old Testament. The author develops a hypothesis that especially (albeit not exclusively) as the author of The Republic, Plato laid the foundations for the political philosophy in general, but also, despite the disapproval of the Athenian democracy he manifested, for the philosophy of democracy, perceived as a kind of order, based on defining the Good by means of dialogue and the prevalence of so-defined Good over any kind of ‘Demiurge’, including a political Demiurge.